(untitled) (Journal of Health, Population and Nutrition, 2011)
To determine the impact of socioeconomic status on plasma trace element status and pregnancy outcomes, 349 pregnant women, aged 15-40 years (mean 27.04 ±2.75 years), recruited at ≤25 weeks (mean 21.76±3.12 weeks) gestational age, were followed up till delivery during which maternal and foetal outcomes were recorded. Plasma copper, iron, and zinc were determined using atomic absorption spectrophotometer while maternal sociodemographic data were obtained using a questionnaire. Except for copper, lower plasma iron and zinc were significantly (p<0.05) higher in women from socioeconomically-disadvantaged groups. Both adverse maternal health and foetal outcomes also seemed to be more prevalent in socioeconomically-disadvantaged women, although without a definite trend. This study has shown that, in economically-disadvantaged setting of developing countries, maternal socioeconomic status impacts on maternal trace element (copper, iron, and zinc) status and health and foetal outcomes. Key words: Maternal nutrition; Morbidity; Pregnancy outcomes; Socioeconomic status; Trace elements; Nigeria DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7858 J HEALTH POPUL NUTR 2011 Apr;29(2):156-162